B Cell–Activating Transcription Factor Plays a Critical Role in the Pathogenesis of Anti–Major Histocompatibility Complex–Induced Obliterative Airway Disease. Issue 4 (4th February 2016) - Xu, Z.; Ramachandran, S.; Gunasekaran, M.; Nayak, D.; Benshoff, N.; Hachem, R.; Gelman, A.; Mohanakumar, T.
Abstract : Antibodies (Abs) against major histocompatibility complex (MHC) results in T helper‐17 (Th17)‐mediated immunity against lung self‐antigens (SAgs), K‐α1 tubulin and collagen V and obliterative airway disease (OAD). Because B cell–activating transcription factor (BATF) controls Th17 and autoimmunity, we proposed that BATF may play a critical role in OAD. Anti‐H2K b was administered intrabronchially into Batf –/– and C57BL/6 mice. Histopathology of the lungs on days 30 and 45 after Ab administration to Batf –/– mice resulted in decreased cellular infiltration, epithelial metaplasia, fibrosis, and obstruction. There was lack of Abs to SAgs, reduction of Sag‐specific interleukin (IL)‐17 T cells, IL‐6, IL‐23, IL‐17, IL‐1β, fibroblast growth factor‐6, and CXCL12 and decreased Janus kinase 2, signal transducer and activator of transcription 3 (STAT3), and retinoid‐related orphan receptor γT. Further, micro‐RNA (miR)‐301a, a regulator of Th17, was reduced in Batf –/– mice in contrast to upregulation of miR‐301a and downregulation of protein inhibitor of activated STAT3 (PIAS3) in anti‐MHC–induced OAD animals. We also demonstrate an increase in miR‐301a in the bronchoalveolar lavage cells from lung transplant recipients with Abs to human leukocyte antigen. This was accompanied by reduction in PIAS3 mRNA. Therefore, we conclude that BATF plays a critical role in the immune responses to SAgs and pathogenesis of anti‐MHC–induced rejection. Targeting BATF should be considered for preventing chronic rejection after human lung transplantation. Abstract : The authors report that the loss of B cell–activating transcription factor (BATF) results in a significant reduction in antibody‐induced pulmonary inflammation and fibrosis in obliterative airway disease, and demonstrate the importance of BATF‐mediated T helper 17 immune responses in the development of cellular and humoral immune responses to lung‐associated self‐antigens.